Sociospatial reading of favela: A comparative analysis from organic Portuguese cities - Loureiro, V. R. T. (2022)
This research decodifies the favelas spatial system through its configuration in com- parison to historical organic structures aiming at searching similar self-organized processes. It is intended to observe in which way the configuration of such areas, read through their spatial patterns, affects their sociospatial dynamics and how it gets closer to common strategies for organizing the urban space: in which way favela reproduces historically consolidated spatial patterns inherent to organic cities? The Theory of The Social Logic of Space (Hillier & Han- son, 1984) is the theoretical, methodological and technical approach for this study, allowing to investigate such phenomena by means of its spatial complexity. The sample consists of 120 set- tlements around the world, explored according to a set of 26 configurational variables (among qualitative and quantitative, both geometric and topological), compared to a group of 45 Por- tuguese medieval towns (representative of organic cities). Findings show that the favelas recog- nized spatial patterns are mostly common to those associated with organic structures. Despite being much denser and apparently labyrinthine shapes, the internal dynamics of the favelas reveal positive global relationships. These settlements behave similarly to consolidated urban systems and share common spatial logics throughout world regions and distinct cultures, fea- ture which allows recognizing the self-organization strategy as essential to their structural and survival process.